Spatiotemporal and demographic variation in the diet of New Zealand lesser short‐tailed bats (Mystacina tuberculata). Issue 15 (9th July 2018) - Czenze, Zenon J.; Tucker, J. Leon; Clare, Elizabeth L.; Littlefair, Joanne E.; Hemprich‐Bennett, David; Oliveira, Hernani F. M.; Brigham, R. Mark; Hickey, Anthony J. R.; Parsons, Stuart
Abstract: Variation in the diet of generalist insectivores can be affected by site‐specific traits including weather, habitat, and season, as well as demographic traits such as reproductive status and age. We used molecular methods to compare diets of three distinct New Zealand populations of lesser short‐tailed bats, Mystacina tuberculata . Summer diets were compared between a southern cold‐temperate (Eglinton) and a northern population (Puroera). Winter diets were compared between Pureora and a subtropical offshore island population (Hauturu). This also permitted seasonal diet comparisons within the Pureora population. Lepidoptera and Diptera accounted for >80% of MOTUs identified from fecal matter at each site/season. The proportion of orders represented within prey and the Simpson diversity index, differed between sites and seasons within the Pureora population. For the Pureora population, the value of the Simpson diversity index was higher in summer than winter and was higher in Pureora compared to Eglinton. Summer Eglinton samples revealed that juvenile diets appeared to be more diverse than other demographic groups. Lactating females had the lowest dietary diversity during summer in Pureora. In Hauturu, we found a significant negative relationship between mean ambient temperature and prey richness. Our data suggest that M. tuberculata incorporate a narrower diversity of terrestrial insects than previously reported. This provides novel insights into foraging behavior and ecological interactions within different habitats. Our study is the first from the Southern Hemisphere to use molecular techniques to examine spatiotemporal variation in the diet of a generalist insectivore that inhabits a contiguous range with several habitat types and climates. Abstract : Our study is the first from the Southern Hemisphere to use molecular techniques to examine spatiotemporal variation in the diet of a generalist insectivore that inhabits a contiguous range with several habitat types and climates. Mystacina tuberculata exhibit site‐specific differences in the proportion of prey orders consumed, and dietary diversity, suggesting that certain orders are more influential in certain sites than others. These differences are likely due to site‐specific differences in habitat type and season. We also provide the first evidence of demographic differences in the diet of M. tuberculata, with juveniles having the broadest diet, and lactating females the most restricted. Photo credit: David Mudge.